Elaboração de um modelo de enfermagem em cuidados paliativos na atenção domiciliar. - Carvalho, Gleyce Any Freire de Lima (2020)
Home nursing care for people in palliative care involves direct management and assistance, based on the theoretical and methodological principles and knowledge of the profession. The nursing care model offers a guiding framework for this assistance. This study aimed to develop a Nursing Care Model for people in palliative care at home. A qualitative, convergent care research was carried out in Natal, Rio Grande do Norte, Brazil. Nineteen nursing professionals participated in the multidisciplinary teams of Home Care Services, selected for convenience. The study was developed in four stages: 1) Insertion 2) Definition of the basic subsidies. In this phase, it was realized: the configuration of theoretical subsidies through the literature review and conceptual definitions; the identification of the profile of people in palliative care in the services; the performance of the survey, data collection that made immersibility possible; and the intersection of care and research actions in the identification of the perception of nursing professionals about the care for people in palliative care at home; 3) Analysis and Interpretation. In this stage, the data was captured and synthesized, through the organizational record and the Atlas Ti.1® software, culminating in the theorization of information and the elaboration of a conceptual structure in the form of a model. 4) Transfer. In this, a focus group was held with the participants to negotiate the proposal, in order to merge into a coherent whole. Finally, attitudes of commitment, transferability and dialogicity with the new knowledge and the use of the model as a practical and reliable instrument of intervention in nursing care were encouraged. The research was approved by the Research Ethics Committee of the Federal University of Rio Grande do Norte, CAAE: 91773018.7.0000.5537. The study elaborated the “Nursing Care Model for people in palliative care at home” based on theoretical nursing concepts and its assistance methodology. The Model aims to guide nursing professionals to provide systematic assistance to people in palliative care in a comprehensive, interdisciplinary and humanized way, valuing the centrality of the person and his family, in promoting quality of life and comfort in the home environment. Caring for home care is a favorable moment for reflecting on nursing know-how for people in palliative care and the role of nurses as an articulator of care, educational and managerial actions among the health team. It concludes the thesis that a model of nursing care based on comfort and quality of life developed with nursing professionals working in home care represents a guide to know-how in nursing in palliative care in this context